2013
DOI: 10.1037/a0032281
|View full text |Cite
|
Sign up to set email alerts
|

Personality and affective forecasting: Trait introverts underpredict the hedonic benefits of acting extraverted.

Abstract: People report enjoying momentary extraverted behavior, and this does not seem to depend on trait levels of introversion-extraversion. Assuming that introverts desire enjoyment, this finding raises the question, why do introverts not act extraverted more often? This research explored a novel explanation, that trait introverts make an affective forecasting error, underpredicting the hedonic benefits of extraverted behavior. Study 1 (n = 97) found that trait introverts forecast less activated positive and pleasan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
98
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(107 citation statements)
references
References 70 publications
7
98
2
Order By: Relevance
“…Lastly, affective states can be measured with a variety of conceptual approaches (Shuman & Scherer, 2014) such as arousal/valence (e.g., Russell, 1980;Zelenski, Whelan, Nealis, Besner, Santoro, Wynn, 2013), power/control , and cognitive complexity (e.g., Reich, Zautra, & Potter, 2001;Reich, Zautra, & Davis, 2003). Accordingly, future work is needed to replicate our findings with different conceptual models of affective states.…”
Section: Limitations and Future Directionsmentioning
confidence: 89%
“…Lastly, affective states can be measured with a variety of conceptual approaches (Shuman & Scherer, 2014) such as arousal/valence (e.g., Russell, 1980;Zelenski, Whelan, Nealis, Besner, Santoro, Wynn, 2013), power/control , and cognitive complexity (e.g., Reich, Zautra, & Potter, 2001;Reich, Zautra, & Davis, 2003). Accordingly, future work is needed to replicate our findings with different conceptual models of affective states.…”
Section: Limitations and Future Directionsmentioning
confidence: 89%
“…Several experimental studies have provided causal evidence that participants who are instructed to act extraverted (e.g., talkative, bold, assertive) report higher levels of PA than those instructed to act introverted (e.g., quiet, passive, reserved) during interactive activities in the lab (Gallagher, Fleeson, & Hoyle, 2011;McNiel & Fleeson, 2006;McNiel, Lowman, & Fleeson, 2010;Smillie, Wilt, Kabbani, Garratt, & Revelle, 2015;Zelenski et al, 2013;Zelenski, Santoro, & Whelan, 2012) (Keyes, 1998) explained 32% of the relation between trait extraversion and PA. Of the five subscales, social contribution (believing that one has something valuable to give, and does give, to society) was the strongest mediator, independently explaining 29% of the trait extraversion-PA relation. To bolster this correlational study with experimental evidence, Smillie, Wilt, and colleagues (Study 2) then investigated whether state measures of social well-being and social contribution mediated the relation between enacted extraversion and increased PA. As a state measure of social contribution, participants reported the percentage to which they "contributed to the discussion tasks", relative to the other two participants.…”
mentioning
confidence: 99%
“…This explanation may apply to extraverts especially since decreases in self-esteem seem to covary with decreases in reward sensitivity (Hervas & Vazquez, 2016). Finally, recent research has found that introverts do not engage in extraverted behavior because they underestimate the positive effects of acting extraverted (Zelenski et al, 2013). Anticipating a future experience may be closely related to reward sensitivity.…”
Section: Mechanisms Underlying Mood Regulationmentioning
confidence: 99%
“…However, this perspective does not preclude the proposal of an intervention that can allow introverts who desire to increase their levels of positive affect to develop new resources. Thus, as important as it may be to train introverts to behave as extraverts (e.g., Zelenski et al, 2013), or to improve the quality of their interpersonal relationships (e.g., Cabello & Fernandez-Berrocal, 2015), it may be relevant to also build positive mood regulation resources (e.g., through psychoeducation, automatizing enjoyment-oriented behaviors, savoring and so on) that allow introverts to adjust the cognitive and motivational processes that can be misaligned by having reduced reward sensitivity. Considering specifically the findings from this research, training positive mood maintenance could be one of the objectives within a hypothetical program conceived to help introverts.…”
Section: Practical Implicationsmentioning
confidence: 99%